Rethinking Popular Nationalism in Gender Key. Approach From Two One-Time Printed - Ledezma Salse, Ana (Revista de Historia Social y de las Mentalidades, 2024)
This article presents a panoramic view of the problematizations around the national, making room for the popular experience as part of the identity construction of the Chilean. To carry out this interpretive exercise, we turn to the only two popular songbooks preserved by Juan Bautista Peralta, published under the pseudonym Juana María Inostroza. Within this interpretative approach, gender emerges as a tool that helps to differentiate popular experiences and enrich the diversity of the “we” built in Chile at the beginning of the 20th century.
Keywords: Nationalism; Popular sectors; Songbooks; Beginning of the 20th century